STUDENTS’ PERSEPTIONS ON THEIR LEARNING STYLES ON ENGLISH CLASS AT STIA NUSANTARA SAKTI KERINCI, JAMBI: NURFITRI, S.Pd., M.Pd - NURFITRI, S.Pd., M.Pd (JURNAL ADMINISTRASI NUSANTARA, 2020)
This study aims to find out what kind of learning styles that each students have in learning English, as well as their perceptions on it . There are three major kinds of learning styles, they are: Visual learning style, Auditory learning style, and Kinesthetic learning style. After figuring out the types of students learning styles, their perceptions are also studied in order to figure out the students’ needs to learn English, so that it will be helpful for the English lecturer to determine any kinds of materials and teaching media that could facilitate the students’ learning styles. The design of the research was descriptive qualitative. The population of the research was the second semester students of STIA Nusa Kerinci, with one class is chosen as the sample of the research by using cluster sampling method. Based on the analysis, it is found that from twenty five students, 13 students are the visual learners and 10 students are auditory learners, and the rest (2) students are kinesthetic learners. Therefore, from interview, it is found that for the visual students they need to learn more by using pictures, videos, and any visual media. For the auditory students, they need more video media with interesting topics. And for the kinesthetic learners, they said that they need more interesting, challenging and interactive media to study English.